THE EFFECT OF DARK CHOCOLATE CONSUMPTION ON REDUCING MENSTRUAL PAIN SCALE (PRIMARY DYSMENORRHEA) IN FEMALE STUDENTS AT SMK 'AZZA WA JALLA BANDAR LAMPUNG IN 2024 - Yuliana, Dewi; Fhara Dilla, Arie (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Providing access to sexual and reproductive health helps individuals improve well-being which contributes to the achievement of SDGs targets. The results of a pre-survey on November 4, 2024 at several vocational schools in Bandar Lampung showed that the highest incidence of primary dysmenorrhea in the last 3 months was at SMK 'Azza Wa Jalla Bandar Lampung as many as 35 students (63.64%) who visited the UKS to ask for pain relievers and rest. The problem of menstrual pain in female students can interfere with daily activities if not treated, such as hampering school activities and causing recurrent discomfort. One of the non-pharmacology to reduce menstrual pain by consuming dark chocolate can relax the body and improve mood simply and practically. The purpose of the research conducted was to determine the effect of giving dark chocolate on reducing the scale of menstrual pain (Primary Dysmenorrhea) in female students at SMK 'Azza Wa Jalla Bandar Lampung. The research conducted applied a pre-experimental design through a one group pretest - posttest design approach. The research sample amounted to 30 female students using purposive sampling technique. The study applied the Numeric Rating Scale (NRS) instrument. The intervention of giving dark chocolate for 2 days. This research was analyzed through the Wilcoxon Signed Ranks Test. The resulting research shows that there is an effect of giving dark chocolate on reducing the scale of menstrual pain (Primary Dysmenorrhea) in female students at SMK 'Azza Wa Jalla Bandar Lampung in 2024 (p-value = 0.000). Thus, it is concluded that the administration of dark chocolate can minimize the scale of menstrual pain. So it is hoped that young women can apply consuming dark chocolate in overcoming menstrual pain this can be done independently without requiring special skills.